Teatre sense parets. A propòsit de les noves dramatúrgies al carrer - Piquer, Adolf (Caplletra. Revista Internacional de Filologia, 2002)
The author applies the methodological basis of the theatre in the street to the theatrical approaches and the particularperformances of Vila-Real’s group Xarxa Teatre. Particularly, he emphasises two factors: the split of the “Italian box” space and its consequences for actors, receivers and technology.